UNRAVELING EMPLOYEE TURNOVER: INSIGHTS FROM LEBANESE RETAIL COMPANIES - Bennett, Emily Claire; Anderson, Samuel John (Current Journal of Human Resource Management (CJHM), 2023)
This research endeavors to provide a nuanced and analytically rigorous examination of the impact of effective leadership on organizational performance, thereby contributing to the ongoing discourse in this field. By anchoring the study in established literature, we aim to elucidate the intricate relationship between leadership efficacy and organizational outcomes. Central to this exploration are key principles encompassing the conceptual elucidation of leadership, its intersection with motivation, and the consequential influence on job performance. Additionally, we delve into the effectiveness of leadership practices, diverse leadership styles, methods of gauging organizational performance, the pivotal role of communication in leadership, and the essential attributes characterizing effective leadership within the purview of managing subordinates. This comprehensive review positions our research within the broader context of advancing the understanding of how adept leadership can steer an organization towards enhanced performance.